Cordicoterapia oral e inflamatória para o tratamento de sibilancia na infância : uso e abuso - Simone Machado Nunes (2009)
The systemic and topical therapy with corticosteroids for asthma treatment is a consensual point in the literature and an important topic in the guidelines on disorder management. Currently, it is the medication with the best results in asthma control, with quick symptoms reduction, significant improvement in inflammation and pulmonary function. Moreover, it is associated with the mortality decrease and hospitalization caused by this disorder. However, the asthma diagnosis is extremely difficult to be confirmed in children under five years old. There is no accurate and objective diagnosis resource for distinguishing, in the group of lactents wheezers, the asthmatics from the transient wheezers due to similar symptoms. In this age range, episodic wheezing is common inchildren who will not contract asthma, mainly in children under 3 years old, and, generally, it is associated with a viral infection. In the estimation, from 60 to 80% of lactents wheezers will not continue to have bronquial obstruction crises in childhood and adolescence. This diagnostic difficulty results in a barrier to propose an efficacious and certain therapy for that age range. Despite this, corticotherapy has been used in lactentswheezers for symptom control and respiratory improvement. Some studies have introduced anti-inflammatory therapy precociously with the purpose of interfering in asthma natural history. Therefore, the aim of this study is to review the literature about corticotherapy use for wheezing in younger children and to evaluate prevalence of it via oral and inhaled inhealth Units in Belo Horizonte. The dissertation is composed of two cientific articles. The first one is an article which reviews corticotherapy efficacy for wheezing treatment in the early years of life. The review includes the period from 1998 to 2008, in the following databases MEDLINE, LILACS and PubMed. Treatment guidelines, review articles, systematic reviews, randomized controlled trials were selected, and evaluated the efficacy of treatment with oral or inhaled corticosteroids in wheezing children in the first years of life. The result of the studies, which investigated corticosteroids efficacy, are still controversial. A significant part of those studies failed to demonstrate benefits, specially related to the impact in natural history of the disorder. Some studies indicate a better symptom control with the use of inhaled corticotherapy for large periods, but this effect does not seem to remain after discontinuation of the drugs. Additionally, no relevant benefits were observed in treatment for wheezing caused by virus. The second article evaluated the prevalence of corticosteroids use in lactent wheezers related to first year of life and correlated with associated factors such as severity, atopic risk, familiar, environmental and demographic features in the studied population. The use of oral and inhaled corticosteroids was observed in 249 (48,7%) and 296 (51,3%) wheezing children, respectively. In recurrent wheezers, the use of oral corticoid was 63,5% and for the inhaled one was 64,3%. An high rate of corticosteroids via oral and inhaled have been used in lactent wheezer in the first year of life, on the assumption that 60% to 80% of those children will not become asthmatic in the future. In addition, the current state of knowledge and the lack of methodologically comparable data render the use of these medications difficult and uncertain.